Business Communication Strategies in Building Brand Awareness on the Instagram Account of UMJ Press Academic Publisher - Ahmad Noval; Dian Istiaty; Syarifuddin Raisul Haq Kusumadiningrat; Tria Patrianti (Indonesian Scientific Publication, 2026)
The rapid development of digital technology has positioned social media as a strategic channel for organisational communication, including for academic publishers seeking to enhance brand visibility. This study examines how UMJ Press utilises Instagram as a digital communication platform to build brand awareness as an academic publisher. Employing a qualitative case study design, data were collected through in-depth interviews with the Instagram account manager and active followers, participatory observation of feed posts, stories, and reels, and documentation of audience interactions. The data were analysed using thematic analysis to identify recurring patterns related to content strategy, visual identity, interaction management, and audience perceptions of brand recognition and recall. The findings indicate that brand awareness is shaped through consistent visual branding, the dominance of educational and informative content, and active engagement practices that encourage audience interaction. Short video formats (reels) and interactive features (stories) were associated with higher engagement patterns as reflected in audience responses such as shares and saves. Brand recognition emerged through consistent design elements and thematic coherence, while brand recall was reflected in participants’ ability to spontaneously associate UMJ Press with academic publishing activities. This study contributes to the literature by extending Integrated Marketing Communication, Uses and Gratifications Theory, and Social Media Engagement perspectives into the context of academic publishing, a sector that has received limited attention in Instagram-based branding research. The findings suggest that strategically managed Instagram communication can support the development of brand awareness within credibility-driven institutional contexts.